Application of the Full Costing Method in Determining Selling Prices and Its Implications for MSME Profitability: A Case Study of Fajrir Cassava Chips - Meyra Rizky Azhary; Sri Ramadhani; Atika (Jurnal Investasi Islam, 2026)
Although accurate production cost calculation is essential for MSME profitability, previous studies have focused mainly on external factors such as financing, financial literacy, and marketing, while the accuracy of production cost determination as a basis for pricing in micro-scale food MSMEs remains underexplored. This study addresses this gap by examining the application of the full costing method in determining production costs and its implications for profit accuracy at Keripik Singkong Fajrir MSME, where business and personal expenses are not yet clearly separated. The study employs a qualitative case study approach, with data collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman thematic analysis model. The full costing method was chosen because it incorporates all production cost components, including raw materials, direct labor, and fixed and variable manufacturing overhead. The findings reveal a total annual production cost of IDR 565,800,000, consisting of raw materials (IDR 447,600,000), direct labor (IDR 97,200,000), and manufacturing overhead (IDR 21,000,000). With total sales of IDR 972,000,000 and a selling price of IDR 50,000 per kilogram, the MSME generated a gross profit of IDR 446,200,000 and an operating profit of IDR 443,200,000 after operating expenses. The results indicate that although the current selling price still produces profit, it is based largely on habit and market considerations rather than accurate cost information, making profitability vulnerable to future cost increases. This study contributes to the literature by highlighting the importance of comprehensive cost calculation and systematic cost recording to support pricing decisions and improve profit reliability in micro-scale food MSMEs.